Vortioxetine Modulates the Regional Signal in First-Episode Drug-Free Major Depressive Disorder at Rest - Xiong, Shihong; Li, Wei; Zhou, Yang; Ren, Hongwei; Lin, Guorong; Zhang, Sheng; Xiang, Xi (Frontiers in Psychiatry, 2022)
Background: Previous studies on brain functional alterations associated with antidepressants for major depressive disorder (MDD) have produced conflicting results because they involved short treatment periods and a variety of compounds. Methods: Resting-state functional magnetic resonance imaging scans were obtained from 25 first-episode drug-free patients with MDD and 25 healthy controls. The patients, who were treated with vortioxetine for 8 weeks, were scanned at two-time points (baseline and week 8 of treatment). The amplitude of low-frequency fluctuation (ALFF) in the imaging data was used to analyze local brain signal alterations associated with antidepressant treatment. Results: Compared with the controls, the patients at baseline showed decreased ALFF values in the right inferior temporal gyrus and increased ALFF values in the left inferior cerebellum, right cingulate gyrus and postcentral gyrus. After 8 weeks of vortioxetine treatment, patients showed increased ALFF values in the bilateral cingulate gyrus, middle temporal gyrus, medial superior frontal gyrus, and inferior cerebellum. Conclusion: This study provided evidence that vortioxetine modulates brain signals in MDD sufferers. These findings contribute to the understanding of how anti-depressants effect brain function.